Tief an des boumes rinden - Vanessa-Nadine Sternath (Recherches Germaniques)
Based on the analysis of tokens of love in Konrad von Würzburg’s novel Trojanerkrieg and of Andreas Hase’s nature guide Bäume. Tief verwurzelt, this article shows that both in the Middle Ages and today, femininity, women, and their vulnerability are symbolically linked to nature and vice versa. They share experiences of violence characterized by patriarchal structures which can ultimately lead to mistreatments or death.